(untitled) (American Journal of Islam and Society, 2009)
InDefense of the Bible containsWalid Saleh’s critical edition of Al-Aqwal al- Qawimah fi îukmal-Naql min al-Kutub al-Qadimah (The Just Verdict on the Permissibility of Quoting from Old Scriptures). This treatise, composed by Ibrahim ibn `Umar al-Biqa`i during the last days of Mamluk rule, sought to defend his commentarial use of the Hebrew Bible and the Christian Gospels to interpret the Qur’an. While many Qur’anic commentators rely heavily on the isra’iliyat genre to support their interpretations of the Qur’an, al-Biqa`i’s tafsir radically departed from the Islamic religious and scholarly practice by quoting directly from the Jewish and Christian scriptures. This hermeneutical decision met with great resistance and criticism from al-Sakhawi, one of Cairo’s leading scholars, who wrote a scathing response in support of the traditional Islamic legal prohibition against the religious use of the Bible, a text believed to have existed only in corrupt form. The question of why al-Biqa`i relied so heavily on the Hebrew Bible and Christian Gospels, and how he defended his decision to do so, is the subject of both the Aqwal and Saleh’s introduction to his critical edition of this medieval text. Saleh’s work not only sheds light on the complexity of Mamluk-era Cairo’s vibrant intellectual milieu, but, more importantly, corrects the contemporary academic bias that Muslims rarely engaged with the Bible during these times ...